Faktor Dukungan Sosial Perilaku Personal Hygiene Genitalia Napi Perempuan di Lapas Kelas IIA Sidoarjo - Nabila Mu'taz Dzakiyya; Mohammad Zainal Fatah (Jurnal Keperawatan Muhammadiyah, 2019)
Female prisoners, who are minority figures in prisons, have fewer opportunities to obtain health facilities and services that support their reproductive health care. Programs and socialization aimed at female prisoners are often ineffective, so they don't get the knowledge they need. Sometimes, their basic needs, such as when they experience menstruation (such as sanitary napkins and clean underwear), are still lacking. The purpose of this study is to describe the social support received by female prisoners in the practice of genital personal hygiene behavior during the period of detention at the Class IIA Sidoarjo Penitentiary. The method used is a qualitative method. The conclusion that can be drawn from this study is, the support received by female prisoners during the detention period to support the behavior of genitalia personal hygiene, namely the family of female prisoners, female prisoners' roommates, to the prison. Support provided in the form of information to the items needed.